2015
DOI: 10.1039/c4dt03892d
|View full text |Cite
|
Sign up to set email alerts
|

Ferutinin as a Ca2+complexone: lipid bilayers, conductometry, FT-IR, NMR studies and DFT-B3LYP calculations

Abstract: Calcium ionophoretic properties of ferutinin were re-evaluated in solvent-containing bilayer lipid membranes. The slopes of conductance-concentration curves suggest that in the presence of a solvent in the membrane the majority of complexes appear to consist of a single terpenoid molecule bound to one Ca ion. By contrast, the stoichiometry of ferutinin-Ca(2+) complexes in acetone determined using the conductometric method was 2 : 1. While the cation-cation selectivity of ferutinin did not change, the cation-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…4, 8). One can suggest that ferutinin acts as Ca 2+ -ionophore that directly increases the inner mitochondrial membrane permeability to Ca 2+ -ions, which was earlier shown for planar lipid bilayer membranes and liposomes (Zamaraeva et al 1997;Abramov et al 2001;Dubis et al 2015).…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…4, 8). One can suggest that ferutinin acts as Ca 2+ -ionophore that directly increases the inner mitochondrial membrane permeability to Ca 2+ -ions, which was earlier shown for planar lipid bilayer membranes and liposomes (Zamaraeva et al 1997;Abramov et al 2001;Dubis et al 2015).…”
Section: Discussionmentioning
confidence: 63%
“…Similarly, earlier works showed that ferutinin at concentrations of 1-50 µM considerably increased Ca 2+ -permeability of thymocytes, platelets, Jurkat T-cell, erythrocytes, mitochondria, and sarcoplasmic reticulum (Zamaraeva et al 1997(Zamaraeva et al , 1999(Zamaraeva et al , 2010Macho et al 2004;Gao et al 2013). Ferutinin interacts strongly with Ca 2+ -ions via the hydroxyl group of ferutinol and the carboxyl oxygen of the complex ether bond (Dubis et al 2015). It was demonstrated previously using FT-IR and NMR data together with theoretical calculations that in the absence of Ca 2+ ions ferutinin molecules formed H-bonded dimers while complexation of Ca 2+ by ferutinin ruptured this hydrogen bond due to spatial re-orientation of the ferutinin molecules from parallel to antiparallel alignment (Zamaraeva et al 1997;Abramov et al 2001;Dubis et al 2015).…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…With time prolonging, there are obviously different intermediates on the surface of the two catalysts. For LaCoO 3 , the intensities of the carboxyl group (1468 cm –1 ), CC species (1557 cm –1 ), enolate species (1629 cm –1 ), and carbonyl group (1683, 1733 cm –1 ) , are increased from 8 min and then disappear at 22 min, whereas the CO 2 (2360 cm –1 ) signal remains stable. This demonstrates that the decomposition rate of intermediates is not easy.…”
Section: Resultsmentioning
confidence: 96%